Diccionario de costarriqueñismos. Índices de mortandad léxica en frases zoonímicas - Jiménez Castro, Marjorie (2012)
This research aims, through a questionnaire of 302 statements applied to 43 informants, to identify zoonimics phrases of the Diccionario de costarriqueñismos by Arturo Agüero, that have been stopped using of or are in the process of misuse in the Greater Metropolitan Area of Costa Rica, which is the lexical mortality rate and what could be the reasons for socio - cultural factors that have contributed to the disappearance. To do this it has been created a database that allows us to systematize the information, seeks to throw a series of data, relevant for studies conducted in the future about the Dicionario de Costarriqueñismos and about the zoonimics phraseologism in the Spanish of Costa Rica.